2019
DOI: 10.1515/zpch-2019-1374
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Differences in Excited-State Properties of Styryl-BODIPY Chromophores upon Change from α- to β-Substitution

Abstract: We present a femtosecond pump-probe UV-Vis broadband transient absorption spectroscopy study of two styryl-substituted BODIPY chromophores with different position of the substituent. The α-substituted isomer shows typical BODIPY-type spectral features, such as sharp absorption and emission bands, a small Stokes shift and an excited-state lifetime in the 4 ns range, which only weakly depends on the solvent. In contrast, β-styryl-BODIPY features much broader steady-state absorption and emission spectra and a lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Therefore, the excited state dynamics of the investigated BODIPY can be described with a series of sequential steps, see Scheme 3. In agreement with previous works [33,[38][39][40], we propose that after light absorption to the excited Franck-Condon state (FC); (i) fast FC relaxation and solvent-related reorganization occurs to form the locally excited state (transient lifetime values ranging from 0.44 ps to 4 ps, τ 1 ); (ii) from here charge separation concomitantly with conformational evolution (associated with BODIPY-core structural changes in the excited state) give rise to the charge transfer state (CT) discussed above (τ 2 in the 50-87 ps range). Indeed, although the methyl groups at the 1,3,5-positions hinder the rotation of the substituent groups at the meso-and β-positions, it was shown that bending of the BODIPY-core occurs in the excited state [38].…”
Section: Kinetic Analysissupporting
confidence: 93%
“…Therefore, the excited state dynamics of the investigated BODIPY can be described with a series of sequential steps, see Scheme 3. In agreement with previous works [33,[38][39][40], we propose that after light absorption to the excited Franck-Condon state (FC); (i) fast FC relaxation and solvent-related reorganization occurs to form the locally excited state (transient lifetime values ranging from 0.44 ps to 4 ps, τ 1 ); (ii) from here charge separation concomitantly with conformational evolution (associated with BODIPY-core structural changes in the excited state) give rise to the charge transfer state (CT) discussed above (τ 2 in the 50-87 ps range). Indeed, although the methyl groups at the 1,3,5-positions hinder the rotation of the substituent groups at the meso-and β-positions, it was shown that bending of the BODIPY-core occurs in the excited state [38].…”
Section: Kinetic Analysissupporting
confidence: 93%
“…58 This opens new opportunities in fluorescence spectroscopy for our other Bodipys, which possess reactive side groups at the βposition. 57,59,60 ■ EXPERIMENTAL SECTION…”
Section: ■ Discussionmentioning
confidence: 99%
“…Moreover, questions on molecular stiffness, which are discussed in cell recognition by means of the glycocalyx, can be assessed by time-resolved fluorescence anisotropy . This opens new opportunities in fluorescence spectroscopy for our other Bodipys, which possess reactive side groups at the β-position. ,, …”
Section: Discussionmentioning
confidence: 99%